Subthalamic deep brain stimulation modulates conscious perception of sensory function in Parkinson's disease. Issue 12 (December 2016) - Cury, Rubens G.; Galhardoni, Ricardo; Teixeira, Manoel J.; dos Santos Ghilardi, Maria G.; Silva, Valquiria; Myczkowski, Martin L.; Marcolin, Marco A.; Barbosa, Egberto R.; Fonoff, Erich T.; Ciampi de Andrade, Daniel
Abstract : Abstract: Subthalamic deep brain stimulation (STN-DBS) is used to treat refractory motor complications in Parkinson disease (PD), but its effects on nonmotor symptoms remain uncertain. Up to 80% of patients with PD may have pain relief after STN-DBS, but it is unknown whether its analgesic properties are related to potential effects on sensory thresholds or secondary to motor improvement. We have previously reported significant and long-lasting pain relief after DBS, which did not correlate with motor symptomatic control. Here we present secondary data exploring the effects of DBS on sensory thresholds in a controlled way and have explored the relationship between these changes and clinical pain and motor improvement after surgery. Thirty-seven patients were prospectively evaluated before STN-DBS and 12 months after the procedure compared with healthy controls. Compared with baseline, patients with PD showed lower thermal and mechanical detection and higher cold pain thresholds after surgery. There were no changes in heat and mechanical pain thresholds. Compared with baseline values in healthy controls, patients with PD had higher thermal and mechanical detection thresholds, which decreased after surgery toward normalization. These sensory changes had no correlation with motor or clinical pain improvement after surgery. These data confirm the existence of sensory abnormalities in PD and suggest that STN-DBS mainly influenced the detection thresholds rather than painful sensations. However, these changes may depend on the specific effects of DBS on somatosensory loops with no correlation to motor or clinical pain improvement. Abstract : Supplemental Digital Content is Available in the Text. Parkinson's disease is associated with sensory deficits that are modified towards correction after deep brain stimulation, which are not correlated to motor improvement.